Konsep Manajemen Pengelolaan Kolam Renang Berbasis Nilai – Nilai Syariah: Studi Kasus Kolam Renang Alifa Medan Sunggal - Ratna Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out the concept and management of the Alifa swimming pool and how the Alifa swimming pool implements the sharia system in it. The research method used is qualitative and descriptive. The types of data used are primary and secondary data. Primary data was obtained through interviews with swimming pool managers, one swimming pool employee and two swimming pool visitors. Secondary data was obtained through literature related to the concept and management of swimming pools. The results of this research show that the concept and management of the Alifa swimming pool is quite good in terms of sharia. Even though the Alifa swimming pool still has one swimming pool and there are no separate swimming pools for men and women, the Alifa swimming pool has a schedule for non-Muslim men and women. Compared to other conventional swimming pools, the Alifa swimming pool looks quite comfortable. However, there needs to be improvement in the management of the Alifa swimming pool so that it meets all halal aspects, as regulated in the DSN-MUI, for example separating swimming pools between men and women and providing proper and closed worship facilities.